Management of the Transport Infrastructure Development Programme in the Czech Republic - Novak, Radek (Communications - Scientific letters of the University of Zilina, 2000)
The article deals with problems of the transport infrastructure in the Czech Republic in all branches and modes of transport. There are discussed some details of the essential principles of the global national project “Transport Infrastructure Development Programme in the Czech Republic”. This is the principal focus of this article. The article is based on various materials and documents of different management levels – especially those of the Ministry of Transport and Communication of the CR. These documents are summarised in the Programme. The article is focused mainly on the explanation of the future trends of rebuilding and modernisation of the transport infrastructure in the CR, especially in terms of road and railway networks. But there are also some comments on the problems of inland waterways development, municipal public transport and air transport.